Finite Element Simulation of Moisture Content Changes of Peeled Banana (Musa x paradisiaca L.) during Drying - Pankaew, Prasan; Janjai, Serm; Nilnont, Wanich; Bala, Bilash Kanti (Naresuan University Journal: Science and Technology (NUJST); Vol 29 No 4 (2021): October-December 2021DO - 10.14456/nujst.2021.39, 2021)
This paper presents finite element simulation of drying of peeled banana. A two-dimensional finite element model was developed for simulation of moisture content changes during drying of peeled banana. The finite element simulation model was programmed in Compaq Visual FORTRAN version 6.5. Classical models for moisture diffusivity, sorption isotherm and volumetric shrinkage of peeled banana were experimentally determined and used in the finite element simulation. The finite element model prediction was compared with the experimental data. The agreement between the simulated moisture content changes and the experimental data was in reasonable agreement with a discrepancy in root mean square error being in the range of 2.2-14.6%. Moisture content change profiles inside peeled banana during drying were predicted and these profiles give a good picture of the moisture movement inside peeled banana during drying. Keywords: Drying, Peeled banana, Finite element, Moisture diffusion